Enhancing two-way communication in disaster management in the EU—practical insights - Vollmer, Maike; Overmeyer, Maike; Kaluza, Benjamin F. (Frontiers in Communication, 2025)
With the increase of natural and complex disasters, involving the population as victims or spontaneous helpers, effective risk communication is a central task for disaster relief organizations and civil protection agencies. At the same time, the increasing role of social media and other platforms where citizens can share information present new opportunities (such as making information from affected areas available to disaster relief organizations) but also challenges (such as rapid spread of misinformation). This requires effective two-way communication between organizations and the population, a communication focusing on active listening and interaction to address population concerns and to enhance mutual understanding. In two recently concluded EU Horizon 2020 projects, this challenge has been addressed from complementary perspectives. In PANDEM-2 (Pandemic Preparedness and Response), different conceptions of two-way communication were discussed in interviews and workshops with agencies, media and independent experts to identify ways through which authorities operationalize such communication. Notably, for the pandemic case, comprehensive data spanning different phases of the disaster management cycle were gathered. The project RiskPACC (Integrating Risk Perception and Action to Enhance Civil Protection-Citizen Interaction), employed a co-creative approach to develop technical, conceptual and strategic solutions to enhance two-way communication between citizens and civil protection authorities. Our findings highlight the imperative of co-creative methodologies involving multiple stakeholders including specific citizen groups, building relationships of trust, harmonization of narratives with collaborating entities, knowledge exchange and a careful handling of social media communication.